Students' Knowledge Level on First Aid For Sports Injuries - Aprizal, Wahyu; Fauzan, Suhaimi; Pramana, Yoga; Fradianto, Ikbal; Mita, Mita (2025)
Background: Sports injuries frequently occur among students during physical activities; however, many remain uninformed about proper first aid procedures, such as the RICE method (Rest, Ice, Compression, Elevation). Objective: This study aims to identify students' knowledge levels regarding first aid for sports injuries at SMA Negeri 7 Pontianak. Methods: This quantitative study employed a descriptive design using a survey method with a Guttman scale questionnaire. The sample consisted of 247 students from grades XI and XII at SMA Negeri 7 Pontianak. Results: The findings revealed that the majority of students possessed good knowledge (54.35%), adequate knowledge (43.5%), and insufficient knowledge (3.2%) regarding the RICE method. Although many students had not been directly exposed to the RICE method, they still demonstrated good knowledge, influenced by other factors such as curriculum or prior learning experiences. Conclusion: The majority of students demonstrated good knowledge regarding the RICE method.